POLA PENGELOLAAN RUANG AREA HUTAN BERBASIS KEARIFAN LOKAL MASYARAKAT DISTRIK AYAMARU TIMUR SELATAN, KABUPATEN MAYBRAT - Jois Kambu; Johni Marwa; Agustinus Murdjoko (Yayasan Nusantara Hasana Berdikari, 2023)
The forest areas space management based on the local wisdom was integrated with the traditional approach of local knowledge of society in forest management. In the forest areas space, there was affected the occurrence of damage to the ecology, poverty, and destruction of the cultural system of society, conflicts of interest and then environmental unsustainability. This research purposed to identified the pattern of utilization of forest areas space management, the rules and customs that applied by indigenous communities in the eastern and southest Ayamaru District, in Maybrat Regency. The data collected on June to August 2023, consists of secondary and primary data. Primary data collected by interviews with the indigenous communities. Indigenous communities in the eastern and southest-Ayamaru District, in Maybrat Regency have established the area of forest exploitation, with the allocation of space for the cultivation area or utility zone, protected areas (hydrological) and the specific ecological zones or landscapes in bahasa is ‘Pamali’ areas (Mbou). The sustainability level of utility space alocation based on local knowledge of Maybrat communities in the eastern and southest in Ayamaru District is categorized as highly sustainable, with 74 % of its natural areas being protected or custodially preserved.